Planning Dakwah Aisyiyah dalam Mengantisipasi Opini Marriage is Scary di Kalangan Remaja Putri Kecamatan Medan Area - Siagian, Salsabilla Amanda Putri; Soiman, Soiman (Universitas Cokroaminoto Yogyakarta, 2025)
Marriage is the most frequently discussed topic by society. Each individual has a different opinion in responding to marriage. Usually this opinion is influenced by personal experience and the surrounding environment. Recently, the topic of marriage is scary has been widely discussed on various social media such as X, TikTok, Instagram and other social media, this can influence teenagers' opinions about marriage. Therefore, systematic da'wah Planning is needed to respond to it. This research aims to describe Aisyiyah's Da'wah Planning in Anticipating the Opinion of Marriage is scary among Young Women in Kecamatan Medan Area. This study applies qualitative descriptive methodology supported by data gathering methods through a combination of in-depth interviews, library research, and social media analysis. The results of the study showed that Aisyiyah da'wah Planning includes: (1) Planning to hold pre-marital classes; (2) utilizing social media as a da'wah medium; and (3) carrying out routine studies.